2011
DOI: 10.1016/j.jtcvs.2010.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral near-infrared spectroscopy during cardiopulmonary bypass predicts superior vena cava oxygen saturation

Abstract: Cerebral near-infrared spectroscopy accurately predicts superior vena cava oxygen saturation and changes in superior vena cava oxygen saturation on cardiopulmonary bypass. The relationship between flank near-infrared spectroscopy and inferior vena cava saturation is not as strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…This reciprocal correlation and predictive value of static and dynamic (acute variations) between the SvcsO2 rcSO2 and were recently confirmed in another similar study [23]. The sample sizes in these two studies are similar to ours.…”
Section: Discussionsupporting
confidence: 89%
“…This reciprocal correlation and predictive value of static and dynamic (acute variations) between the SvcsO2 rcSO2 and were recently confirmed in another similar study [23]. The sample sizes in these two studies are similar to ours.…”
Section: Discussionsupporting
confidence: 89%
“…20 Third, it has been shown that the rate of withdrawal influences the jugular venous saturation, resulting in higher saturation with faster withdrawal. 74 Use of continuous saturation monitors might be a potential solution to decrease such error, but when looking at studies using in-line saturation monitors, 14,[25][26][27] greater negative bias is found. Fourth, it is not really possible to draw blood from the jugular bulb or superior vena cava in preterm infants.…”
Section: Validation With Blood Samplesmentioning
confidence: 99%
“…В отличие от ЦВД, в данной клинической ситуа ции, rSO 2 снижается достаточно быстро, вызывая необходи мость поиска причины. Эпизоды асимметричной выраженной десатурации могут выявляться иногда и при манипуляциях на сердце при операциях без ИК [3,15,22,32].…”
Section: факторы риска развития но при кардиохирургических операцияхunclassified